A Monolithic CMOS Autocompensated Sensor Transducer for Capacitive Measuring Systems - Chiang, Cheng-Ta; Wang, Chi-Shen; Huang, Yu-Chung (My University, 2008)
In this paper, a monolithic complimentary metaloxide-semiconductor (CMOS) autocompensated sensor transducer for capacitive measuring systems is newly presented. The proposed converter is compact and robust to integrate in capacitive measuring systems. The proposed autocompensated sensor transducer is attractive due to the fact that a digitized signal is produced without realizing the analog-to-digital converter. Hence, the hardware cost could be reduced. Furthermore, the output signal of the proposed transducer is a pulse stream; it could be easily sent over a wide range of transmission media, such as package switch networks (PSNs), radios, and optical, infrared (IR), and ultrasonic media. Another innovation is that the proposed automatic compensation circuits enhance and compensate the linear relation between the variable capacitance of the detected sensor and the output digital frequency over a wide dynamic frequency range. Measurement results have successfully verified the functions and the performance of the proposed autocompensated sensor transducer and confirmed that it is possible to apply it to the air pressure sensor. The area of this chip is 940 x 1080 mu m(2) and the power consumption is 6.4 mW. The proposed transducer is not only suitable for capacitive measuring systems but also practical for application in the front-end systems of the wireless sensor network.
Keywords: Capacitive sensor; complimentary metal-oxide-semiconductor (CMOS); sensor interface; sensor transducer; signal conditioning